Evaluación del cumplimiento de la normativa legal relacionada al impuesto único al banano en la empresa Guaylala - Mueses Gomez, Jonathan Daniel (2015)
The banana industry at country level has been a significant contribution to the national economy, generating huge revenues that are located in one of the main source of income, because of that the tax authority has established a payment of 2% of the single tax banana, which is why it was necessary to do a study to establish a basic procedure to follow under the company that has been studied is the company Guaylalá Pasaje Canton has been presenting problems in this regard, what has meant that the watchdog punish the company, this has led to low profitability and profit from it. The methodology used was through the scientific method, using correlational and exploratory research, where it was determined that the problem of study is the application of legislation tax, and specifically the single tax banana, through probing through instruments and dialogue with the owner, it was established that the company has little knowledge of enforcement, this has meant that the financial statements are unreasonable and that the information is unreliable, concluding that the lack of control has influenced in the tax aspect and therefore in decision making, and that when applied the rules is reflected poor training, and ends by recommending include internal policies for the payment of this tax as well as constant training specifically to the accounting area It is dedicated to the management of these values, and validate this through periodic evaluations to maintain order and clarity of transactions in the company, hoping that the institution has real benefits and profits by law